2019
DOI: 10.1016/j.eap.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Will peak car observed in the North occur in the South? A demographic approach with case studies of Montreal, Lille, Juarez and Puebla

Abstract: In most developed countries, total car driving is stagnating since the early 2000s. This trend can be attributed primarily to people living in the largest urban areas: trips have become less frequent (with unbroken workdays) and less exclusively taken by car (as more young adults adopt multimodal behaviors). A review of the literature shows that demography is an important factor explaining peak car. It is examined through case studies from cities of different level of development.To represent developed economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(13 reference statements)
0
4
0
1
Order By: Relevance
“…Factors related to life situation, such as living alone and childlessness, have a reducing impact on car ownership and on having a driving licence [11]. Some Western European countries, like the UK, the Netherlands, Sweden and Italy, have already seen the peak car use during the first five years of the millennium, resulting to a decline of car use after that point [12] and in the United States the growth halted in 2000 [13]. However, there is evidence of a continuing increase of total vehicle kilometres again after 2009 is the USA [14].…”
Section: Current Situation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Factors related to life situation, such as living alone and childlessness, have a reducing impact on car ownership and on having a driving licence [11]. Some Western European countries, like the UK, the Netherlands, Sweden and Italy, have already seen the peak car use during the first five years of the millennium, resulting to a decline of car use after that point [12] and in the United States the growth halted in 2000 [13]. However, there is evidence of a continuing increase of total vehicle kilometres again after 2009 is the USA [14].…”
Section: Current Situation Analysismentioning
confidence: 99%
“…However, there is evidence of a continuing increase of total vehicle kilometres again after 2009 is the USA [14]. In addition to this, many other developed countries, such as Germany, France, Norway, the UK and Japan show a clear stabilisation in annual kilometres driven, and the change in car use has been particularly apparent in the 20-29 age group [13].…”
Section: Current Situation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Entre 2007 et 2012, le transport des marchandises a par exemple diminué de 18 %. Certains démontrent avec pertinence que nous aurions atteint le « peak car » (MADRE, 2018 ;CORNUT, 2017). Et au-delà des périodes de crise, serait-il possible d'aller vers un découplage entre la croissance économique et celle des transports ?…”
Section: Toujours Moins ?unclassified
“…They confirmed that the generation effect existed and population aging would contribute to a reduction in the level of car ownership. In addition, Bussière et al [20] demonstrated that the peak car phenomenon is projected to occur in developing countries due to the demographic transition, including a slowdown of population growth and population aging.…”
Section: Introductionmentioning
confidence: 99%